Sleep Disorders Among Individuals With Developmental Disabilities: A Comprehensive Analysis - Chichevska Jovanova, Natasha; Ilieska, Valerija; Rashikj Canevska, Olivera; Ramo Akgun, Nergis (European Journal of Special Education Research, 2024)
Sleep problems in individuals with developmental disabilities pose significant challenges for them and their families. This paper aims to examine the types of sleep problems in these individuals, the causes of these issues, and their impact on daily life. Through the analysis of available literature and research conducted on a sample of 67 individuals with special needs and their parents, data are obtained on the prevalence of sleep problems, influential factors, and methods for coping with them. The results show that sleep problems in individuals with developmental disabilities are significant and can seriously impact their quality of life. More than 70% of parents state that the lack of sleep negatively affects their daily life and professional activities. The main causes of sleep problems have been identified as sensory disturbances, melatonin deficiency, and other health issues related to the child's condition. Additionally, 73.4% of parents report that they cope with their children's sleep problems independently. These findings suggest a need for improved strategies and interventions for managing sleep in individuals with developmental disabilities, including enhanced support for parents. The significance of these findings lies in highlighting the need for the development of specialized programs and interventions that will help improve the quality of life for these individuals and their families.
Keywords: sleep problems, individuals with developmental disabilities, autism, cerebral palsy, Down syndrome, sleep quality, interventions, parental support